Carotid bifurcation atheromatosis Diagnostic approach and indications for surgical treatment - Esperón Percovich, Alejandro (Cirugía del Uruguay, 1998)
Atherosclerotic dísease of the carotid bifurcatíon is a clear example of controversy about díagnostic methodology and therapeutíc handling. An example of that is the importance gíven in the last times to the realízation of multicentríc and randomízed prospectíve clínica! tríals to assess standards. In this paper we realíze an upgrade of the most relevant epidemíologíca/, etíopathogeníc and anatomopathologíca! aspects of thís disease. We analyze clínica/ presentatíons, paraclínic díagnostíc methods and diagnostic algoríthms. Final/y, we díscuss the indícations for surgica/ treatment by means of prospectíve clínica! rehearsa/ and internatíonal recommendatíons.